The productivist conception of education: The trajectory of university students (Research, Society and Development, 2021)
The Federal Constitution of 1988 provides that the primacy of work is the basis of the social order and that education is a right for all and a duty of the State and the family. It is important in this article to describe the way in which the Brazilian State fails when it does not observe that guaranteeing access to federal public higher education is also ensuring the student's permanence in the learning process until its conclusion. Thus, exploratory research was applied, with a hypothetical-deductive approach methodology and bibliographic procedure method, concomitant with field study. The results show that there is a relationship between education policies in Brazil and the phenomenon of job insecurity and university evasion. It is concluded that the productivist conception of education in Brazil reinforces the problems that involve the students' permanence in the federal public education of superior level. In field research, which 4 (four) students from the Federal University of Pará - UFPA were interviewed, the data are unanimous in the sense that students who have low family income, because within their families, the income comes from precarious work, they face with uncertainty their permanence in the university course due to the costs of commuting, food and didactic material, a situation that compels them to also practice precarious forms of work, such as the sale of products, so that they can remain in the learning process.